HUBUNGAN PERSEPSI SISWA TERHADAP PROGRAM ADIWIYATA DENGAN SIKAP PEDULI LINGKUNGAN DI SEKOLAH DASAR - Ririn Indriani; Guslinda Guslinda (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The research is aimed to find: (1) the perception of fifth grade students about Adiwiyata program in SDN 110 Pekanbaru, (2) the environmental awareness attitude of fifth grade student in SDN 110 Pekanbaru and, (3) the correlation between perception of fifth grade students about Adiwiyata program and their environmental awareness in SDN 110 Pekanbaru. Meanwhile, the research is categorized as quantitative research with correlational approach. As sampling method, the research is used simple random sampling which is consist of a whole student of fifth grade students in SDN 110 Pekanbaru as the sample. Besides, two questionnaires, which are the perception of students about Adiwiyata and the environmental awareness attitude, is used to collect the data. The research also used statistical analysis in analyzing the findings. Based on the research findings, it can be concluded that the perception of fifth grade students about Adiwiyata program is about mediocre level with percentage 64% and their environmental awareness also at same level with percentage 73%. Besides, the hypothesis result concluded that the correlation between students perception about Adiwiyata program in SDN 110 Pekanbaru and their environmental awareness attitude can be considered at strong level where the correlational value is 0.636. The significant calculation also shown the result where tcalculation 5.417 > ttabel 1.68. Therefore, ho is rejected and ha is accepted, it means there are significant correlation between students’ perception and their environmental awareness attitude in SDN 110 Pekanbaru.